2015
DOI: 10.5423/ppj.oa.03.2015.0033
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Fungicide Sensitivity and Genetic Diversity among Colletotrichum Species in Sweet Persimmon

Abstract: Anthracnose, caused by Colletotrichum gloeosporioides (C. gloeosporioides; Teleomorph: Glomerella cingulata), is the most destructive disease that affects sweet persimmon production worldwide. However, the biology, ecology, and genetic variations of C. gloeosporioides remain largely unknown. Therefore, in this study, the development of fungicide resistance and genetic diversity among an anthracnose pathogen population with different geographical origins and the exposure of this population to different cultivat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…The maximum inhibitory effect of pyrimethanil was 85% at 3,000 μg/ml. Based on these results, 50% effective concentration (EC 50 ) and EC 90 values were estimated (Gang et al, 2015; Matheron and Porchas, 2000). Fludioxonil showed the lowest EC 50 value of < 0.1 μg/ml, and pyrimethanil showed the highest of 50 μg/ml (Table 2).…”
mentioning
confidence: 99%
“…The maximum inhibitory effect of pyrimethanil was 85% at 3,000 μg/ml. Based on these results, 50% effective concentration (EC 50 ) and EC 90 values were estimated (Gang et al, 2015; Matheron and Porchas, 2000). Fludioxonil showed the lowest EC 50 value of < 0.1 μg/ml, and pyrimethanil showed the highest of 50 μg/ml (Table 2).…”
mentioning
confidence: 99%
“…In addition, the TEF-1α gene and β-tubulin gene were widely employed in the PCR-RFLP technique because they are easy to use taxonomically. The β-tubulin gene information is often used to study the identification of a pathogen or population (Donaldson et al, 1995; Dubey et al, 2014; Gang et al, 2015; Kim and Min, 2004). However, this study showed that β-tubulin RFLP and phylogenetic analysis Fusarium wilt pathogen is not significantly different from other pathogen isolates.…”
Section: Discussionmentioning
confidence: 99%
“…The 0 signified absence while 1 signified the presence of a particular band. Based on PCR-RFLP analysis, unweighted pair group method with arithmetic average (UPGMA) method dendrograms were determined via genetic variance between the isolates and then discriminant analysis and construction according to linear combinations of the variables was used to determine the maximum separation between the isolates using XLSTAT program (www.xlstat.com) (Gang et al, 2015). …”
Section: Methodsmentioning
confidence: 99%
“…Development of cultivars with a shorter ripening period or with a thicker waxy cuticle may allow the fruit to escape infection by the fungus (Harp et al, 2008; Lewis-Ivey et al, 2004). Chemical control is among the most commonly used strategies for management of fungal diseases (Gang et al, 2015). Chemical control of anthracnose includes use of benzimidazoles, strobilurins, dicarboximides, and demethylation inhibitors which are single-site mode-of-action fungicides (Young et al, 2010).…”
mentioning
confidence: 99%
“…Resistance arising from mutations in target proteins is reported for single-site inhibitors and there is less risk of developing resistance with multi-site inhibitors (FRAC, 2014). Monitoring the development of fungicide resistance is necessary to (i) detect for selection of resistant phenotypes after prolonged chemical use, (ii) streamline chemical control strategies and cost associated with chemical use, and (iii) reduce environmental impact due to accumulation of fungicides (Gang et al, 2015). This study was, therefore, conducted to determine the sensitivity of Fusarium and Colletotrichum isolates infecting bell pepper to fungicides with different modes of action.…”
mentioning
confidence: 99%